7 - Libertés académiques, syndicalisme et politique en Côte d’Ivoire - Goin Bi Zamblé Théodore, (Journal of Higher Education in Africa, 2011)
The year 1990 marks the return to multiparty politics in Côte d’Ivoire, since the university has become a highly politicized institution. Indeed, this pe- riod saw the birth of FESCI prove to be an essential link in the political demands of opposition parties. This has resulted in numerous interventions by the police on university campuses Ivorian. However, with the coup of 1999 and 2000 elections, the opposition then took over the filling. FESCI becomes the all-powerful student union, which lays down the law on univer- sity campuses Ivorian. Academic freedom no longer exists, and students and teachers are often beaten, in total impunity. Côte d’Ivoire academics are faced with the violation of academic freedom by students FESCI members, but they cannot because of their political interests to take responsibility forfinding appropriate measures to respect academic freedom. The current chal- lenge is to academics than their Ivorian political divide together to advocate for the respect of their academic freedom.